A study on contact and vibration characteristics of marine Cross-Connect gear considering system deformation and multiple operating modes - Jingyi Gong; Bing Yuan; Geng Liu (International Journal of Electrical Power & Energy Systems)
The marine Cross-Connect Gear(CCG) exhibits varying transmission chains under different operating modes, with significant differences in system flexibility that directly affect the actual contact state of gear pairs and the coupled dynamic characteristics of the system. In this paper, the Timoshenko beam and the sliced mesh elements are coupled at multiple points along the axial direction. The coupling relationship between the system deformation and the tooth surface contact state is established. Considering the influence of system deformation, a contact analysis method for the CCG is proposed and validated by comparison with a three-dimensional contact finite element model. Furthermore, a dynamic modeling method for CCG with different configurations and operating modes is developed based on the generalized finite element method. The influence of gearbox series connection and transmission power on the contact and vibration characteristics of the CCG under various operating modes is investigated. Finally, the effectiveness of the dynamic modeling method is verified through experimental research. The results indicate significant differences in the contact state and vibration response between the single-gearbox operating mode and the multi-gearbox series operating mode. Under the series-connected gearbox operating mode, the meshing force and transmission power of adjacent gearboxes substantially influence the bending deformation of the shaft system, with herringbone gear pairs prone to uneven load distribution. Series-connected gearbox operating induces coupled resonance modes, resulting in substantial coupling vibrations at the bearings. Increased transmission power exacerbates the misalignment of helical gear tooth surfaces and the uneven distribution of load.